HUBUNGAN RETURN ON ASSETS YANG DIPENGARUHI PENDAPATAN BAGI HASIL - Vitaningrum, Mineva Riskawati; Mubarokah, Isro'iyatul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.05.TAHUN.2021DO - 10.24843/EEB.2021.v10.i05.p02, 2021)
The majority of the population in Indonesia is Muslim, where there has been a need to invest, finance business and accommodate funds based on Sharia principles. The activities of Islamic financial institutions with the most popular profit sharing principles are musharaka and mudharabah. The purpose of this study is to determine the relationship between Return On Assets which is influenced by revenue sharing, represented by mudharabah income and musyarakah income. The population of this research is syriah commercial banks which are registered at www.ojk.go.id . The research data uses quarterly financial reports from 2017-2019. This research is a quantitative type with hypothesis testing using SPSS ver.23. The test used multiple linear analysis test, t test, and F test. The results of the study showed that mudharabah income had an effect on ROA. Musyarakah income has no effect on ROA, this is evidenced by the t-count statistical test of -1.924 and t-table of 2.002 where t count is smaller than t table (t count <t table). Simultaneously, mudharabah income and musyarakan income have an effect on ROA. This is indicated by the results of the f-test Fcount of 6.485 with a significance value of 0.003 <0.05 and a value of 3.16 for Ftable, then the value of Fcount> Ftable with an influence value of 18.5%.